Proceedings of the 44th IEEE Conference on Decision and Control
DOI: 10.1109/cdc.2005.1582577
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Low-Cost Test-Bed for Undergraduate Education in UAVs

Abstract: This article describes the efforts undertaken at the School of Aerospace Engineering at the Georgia Institute of Technology for the development of a low-cost Unmanned Aerial Vehicle (UAV) test-bed for educational purposes. The objective of this test-bed is to provide an avenue for the involvement of undergraduate students (primarily) and graduate students (secondarily) in UAV research. The complete design and development of all hardware interfaces of the UAV platform including the on-board autopilot is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The on-board autopilot is based on the Rabbit RCM-3400 micro-controller (30 MHz with 512 KB RAM) and provides data acquisition, processing, and communication with the ground station, in addition to all UAV control functions. Further details about the UAV platform, autopilot and HILS set-up can be found in [6] and [7].…”
Section: A Hardware Overviewmentioning
confidence: 99%
“…The on-board autopilot is based on the Rabbit RCM-3400 micro-controller (30 MHz with 512 KB RAM) and provides data acquisition, processing, and communication with the ground station, in addition to all UAV control functions. Further details about the UAV platform, autopilot and HILS set-up can be found in [6] and [7].…”
Section: A Hardware Overviewmentioning
confidence: 99%
“…Developing a UAV research platform to validate these new principles and technologies is of great importance, and so it is no surprise that many UAV testbeds have been developed by various academic groups, e.g., [9,20,25,26,32,36,38,40,42]. The main goal in building our testbed is to develop a lowcost and reliable fixed-wing UAV platform that can be used to implement relatively complex control algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the UAV research group at the University of Minnesota have developed a low-cost UAV testbed [11,38], which is mostly built of commercial-off-the-shelf (COTS) components and uses the radio-controlled (R/C) fixed-wing UAV, Ultra Stick 25e, as the main test aircraft. Another low-cost UAV platform, based on the R/C Goldberg Decathlon ARF airframe, has been developed at Georgia Tech [26] for educational purposes. The UAV research platform [20] uses the low-cost open source autopilot, Ardupilot Mega, and the Aero Testbed at the University of Illinois uses the Paparazzi autopilot, which is also low-cost and open source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple Rabbit Semiconductor RCM-3400 TM microcontroller is used to perform complementary filtering data fusion using a limited computational power. In the same spirit, in (Jung et al, 2005), a low-cost testbed for UAVs is presented. It is reported that the main advantage of designing such an autopilot from scratch is that, by contrast to commercially available products (Cloud Cap Technologies, 2004;Micro Pilot, 2004), it provides full access to the internal control structures.…”
Section: Introductionmentioning
confidence: 99%